(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
In the article an analysis is conducted in theory-methodological bases of development of conception of social responsibility of business. The evolution of scientific approaches is considered in relation to forming of corporate social responsibility. Certainly and the role of parties concerned is reasonable in stimulation of input of principles of socially responsible business on domestic enterprises